Soil Moisture 2019
DOI: 10.5772/intechopen.80252
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Inertia-Based Method for Estimating Soil Moisture

Abstract: Thermal inertia is a parameter that characterizes a property of soil that is defined as the square root of the product of the volumetric heat capacity and thermal conductivity. Both properties increase as soil moisture increases. Therefore, soil moisture can be inversely determined using thermal inertia if a relationship between the parameters is obtained in advance. In this chapter, methods for estimating surface soil moisture using thermal inertia are comprehensively reviewed, with emphases on the followings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…It was indicated that the GOES-8 satellite imagery derived LST increased with the decrease of observed SSM (Sun and Pinker 2004). Furthermore, the daily LST difference is negatively related to the thermal inertia of soil, while thermal inertia increases with soil moisture increase (Matsushima 2018;Paruta et al 2020) (Zhuang et al 2023).…”
Section: Land Surface Temperature and Air Temperaturementioning
confidence: 99%
“…It was indicated that the GOES-8 satellite imagery derived LST increased with the decrease of observed SSM (Sun and Pinker 2004). Furthermore, the daily LST difference is negatively related to the thermal inertia of soil, while thermal inertia increases with soil moisture increase (Matsushima 2018;Paruta et al 2020) (Zhuang et al 2023).…”
Section: Land Surface Temperature and Air Temperaturementioning
confidence: 99%
“…LST dominates the pattern of potential evapotranspiration and plays an essential role in SSM retrieval [35], for example, the GOES-8 satellite imager derived LST increases with the decrease of observed SSM [36]. Furthermore, the daily LST difference is related to the thermal inertia of soil with a negative relationship, while thermal inertia increases with soil moisture increase [8,37]. Thus, the daily LST difference between daytime and nighttime was also selected as a predictor variable.…”
Section: Land Surface Features and Precipitationmentioning
confidence: 99%